الحماية القانونية للتطبيقات الذكية: Legal protection for smart applications - Alshuaibi, Nasr Muhammad (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث نعيش اليوم في عالم يعتمد بشكل كبير على الوسائل الحديثة التي لم تعرفها العصور القديمة ، ولمواكبة هذا التطور بات من الضروري أن تتسلح المجتمعات بوسائل العصر الجديد حتى تتمكن من مجابهة العالم وتعاملاته الذكية، وكما نرى اليوم واقع تعاملاتنا اليومية عبر التطبيقات الذكية في الدوائر أو المؤسسات وغير ذلك، وما لها من دور كبير في تخزين المعلومات ومعالجتها واسترجاعها بكل ما يتعلق بالقيمة المالية أو المعنوية، ولهذا تتزايد أهمية هذه التطبيقات مما يتوجب المطالبة بتوفير الحماية القانونية الكافية لها، وكما نلاحظ مايشهده العالم من تطور متسارع وبصورة مستمرة في برامج التطبيقات الذكية لإرضاء جمهور المتعاملين وتعدد أنوعها المختلفة وكما هو معلوم بأن برامج التطبيقات الذكية منتشرة على نطاق واسع وفي متناول الجميع ليسر تخزين المعلومات بدقة متناهية وبأقل الخسائر وسرعة الوصول للمعلومة. يلخص البحث أن الحماية القانونية للتطبيقات الذكية هي مسألة جديدة تتطلب إدخال تشريعات وتعديلات على قانون الملكية الفكرية حيث إن هذه الاختراعات أو الأعمال لا تتميز فقط عن الاختراعات التقليدية، ولكن أيضا عن برامج الكمبيوتر. في الوقت الحاضر، نشهد وتيرة سريعة للاختراعات، خاصة في المجال التقني، وفي المستقبل سنواجه أيضًا الذكاء الاصطناعي والواقع الافتراضي والمعزز، مما يستدعي الحاجة إلى تشريعات لمواكبة هذه الوتيرة. ABSTRACT We live today in a world that relies heavily on modern means that were not known in ancient times. To keep pace with this development, it has become necessary for societies to arm themselves with new age means so that they can confront the world and its smart dealings. As we see today the reality of our daily dealings through smart applications in departments, institutions, etc. This, and their major role in storing, processing and retrieving information in everything related to financial or moral value, is why the importance of these applications is increasing, which requires the provision of adequate legal protection for them, and as we notice what the world is witnessing. There is a rapid and continuous development in smart application programs to satisfy the customer audience and the multiplicity of their different types, and as it is known that smart application programs are widespread and accessible to everyone, to facilitate the storage of information with extreme accuracy, with minimal losses, and quick access to information. The research summarizes that legal protection for smart applications is a new issue that requires the introduction of legislation and amendments to intellectual property law, as these inventions or works are not only distinguished from traditional inventions but also from computer programs. Nowadays, we are witnessing a rapid pace of inventions, especially in the technical field, and in the future, we will also face artificial intelligence, virtual and augmented reality, which calls for the need for legislation to keep up with this pace.